Evangelical sermons and idealization of female Behavior: a bakhtinian analysis of the third party's voice In a discourse - Petrus, Wilton; Santos, Nadson Araujo dos; Pugina, Rosana Leticia [UNESP] (Editora Univ Pontificia Univ Catolica Rio Grande Sul-edipucrs, 2021)
This paper aimed to analyze the authoritative third party voice in the discourse present in sermons of evangelical pastors, regarding the presence of an ideal of female submission, in order to problematize the place and role of women in society. This is a qualitative, exploratory research, in which three videos available on the internet and biblical texts that are used as a voice of authority, dictating rules about the condition of women were analyzed. The methodology was characterized by the dialogic discourse analysis. We tried to understand, from the sermons, how the pastors think about the social construction of the place of women, attending to the biblical precepts of the Pentecostal and Neo-Pentecostal Christian faith. To do so, Bakhtin's (2011) and Volochinov's (2017) reflections on discourse were used, as well as Beauvoir's (1967) thoughts on gender frames. The results of the analysis showed that the patriarchal gear depends on the obedience and submission of evangelical women inside and outside the churches to work.
Keywords: Evangelical sermons; Female behavior; The third party in the discourse